Meear FIRE - Augmented Reality Fire Extinguisher Application For Fire Safety Training - Muhammad Fahmi, Mohd Razi (2023)
The MeeAR Fire project presents the development of an Augmented Reality Fire Extinguisher Application for Fire Safety Training aimed at enhancing fire safety training. This innovative application allows users to interact with virtual fire scenarios using AR technology, simulating realistic emergency situations. Using the PASS (Pull, Aim, Squeeze, Sweep) method, users can familiarise themselves with the proper techniques for effectively operating a fire extinguisher. Additionally, the application offers comprehensive educational content on fire extinguishers categorised for easy access and understanding. Users can also test their knowledge through interactive quizzes provided within the application. One of the critical advantages of MeeAR Fire is its flexibility, enabling users to learn fire safety principles at their convenience and eliminating the need for attending traditional fire safety instruction sessions. The application provides an engaging and immersive learning experience, empowering individuals to acquire essential fire safety skills wherever and whenever they desire. By integrating AR technology and interactive features, MeeAR Fire aims to enhance fire safety training and improve user preparedness for fire emergencies.